(3GOGH GdYGde hGdeJYdes - (3GdMSjf Hf GdbGSe Hf eMeO Hf Ydj, Gdjefj,J (B1050 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdgGOi Edi WQjb GdUhGH hHYO agPg cQGQjS efJNHI ef cJGH LhGgQ GdYbOjf ai aVd GdTQajf TQa GdYde GdLdi hGdfSH GdfHhi s
(3BNQgG (B:s
(3Yf GHf YHGS QVi Gddg YfgeG Cf fHi Gddg Udi Gdgd Ydjg hSde bGd Cf GdgOi GdUGdM hGdSeJ GdUGdM hGdGbJUGO LRA ef NeSI hYTQjf LRAkG ef GdfHhI MJi jchfhG ef NjQ GdfGS CSdGakG gPG BNQ eG JjSQ LeYg ef BOGH GdYdeGA hGdeJYdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B252 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B41s
(3eUOQ GbJfGA GdCUd (B:s
(3GdGeHQhRjGfG s
Keywords: (3GdSjGSI hGdGLJeGYs